Effects of pubertal timing on deviant behaviors in Taiwan: A longitudinal analysis of 7th- to 12th-grade adolescents. (July 2015) - Tsai, Meng-Che; Strong, Carol; Lin, Chung-Ying
Abstract: We investigated the relationship between pubertal timing and deviant behaviors in Taiwan using Taiwan Youth Project (TYP) data. The TYP used multistage-stratified and class-clustered methods in 40 randomly selected schools. We analyzed 1541 adolescents (770 boys; 50.0%) who self-reported their deviant behaviors in 7th, 8th, 10th, and 12th grades. Participants were assigned to early- ( n  = 244; 15.8%), on-time- ( n  = 992; 64.4%), and late- ( n  = 305; 19.8%) puberty groups, and one-way analysis of variance and latent growth modeling were used to examine the frequency of deviant behaviors between them. Early-puberty adolescents had more deviant behaviors (mean = 0.43, SD = 0.74) than did late-puberty adolescents during 7th grade (mean = 0.27, SD = 0.59; p  = 0.004), but not after 8th grade. There were no significant differences in the deviance level between on-time-puberty and early- and late-puberty adolescents. Moreover, puberty was not correlated with the growth of deviant behaviors, which decreased with age. However, boys seemed to engage in more deviant behaviors at the beginning, but their engagement seemed to decline faster than it did for girls. In sum, the deviance of early-puberty adolescents seemed to diminish as they got older.